3C laboratory measurement using laser interferometer - Lebedev, Maxim; Bona, Andrej; Pevzner, Roman; Lebedeva, Maria; Mikhaltsevitch, Vassili; Gale, Nickolas; Gurevich, Boris (CSIRO, 2012)
We are presenting a technique for laboratory measurements of the velocities and polarisations of compressional and shear waves in rock samples using a laser Doppler interferometer (LDI). Such measurements dramatically improve estimations of anisotropy. LDI can measure the particle velocity of a small (0.01 mm2) element of the sample’s surface along the direction of the laser beam. By measuring the particle velocity of the same surface element in three independent directions and transforming them to Cartesian coordinates, we obtain three components of the particle velocity vector. Therefore LDI can be used as a localized threes component (3C) receiver of acoustic waves, and, together with a piezoelectric transducer or a pulsed laser as a source, can simulate a 3C seismic experiment in the laboratory. Performing such 3C measurements at various locations on the sample’s surface produces a 3C seismogram, which can be used to separate P and two S waves, and to find polarisations and traveltimes of these waves. A ‘walk away’ laboratory experiment demonstrates high accuracy of the method. The measured data matches very well with the results from the analytical modelling. From our results, we can conclude that it is possible to characterize elasticity properties of materials from the described measurements. In particular, we are able to determine: 1) the angle between the particle movement and the direction of the wave propagation, i.e. the polarisation, 2) the types of waves and 3) the arrival times of the wave at the point and thus the wave velocities.